Preparation method of nano material based on active metal oxide and rare earth oxide
Through the preparation method based on active metal oxides and rare earth oxides, combined with the use of nitric acid hydrolysis and citric acid solutions, the problems of uneven carbon residue and particle size distribution in nanomaterials were solved, and the nanometers with high purity and uniformity were achieved Material preparation reduces production costs.
Patent Information
- Application Number
- CN202411107627.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing nanomaterial synthesis methods, there are problems such as carbon residue, easy agglomeration, uneven particle size distribution, calcination under atmosphere and low material purity, resulting in poor performance and high production costs.
Using the preparation method based on active metal oxides and rare earth oxides, the formation of colloids is carried out after secondary hydrolysis and low-temperature calcination in the air to remove organic matter and carbon elements to form Nanomaterial with high purity and uniformity.
The preparation of nanomaterials with low calcining temperature, controllable grain morphology, no carbon residue and high powder purity is achieved, which improves the purity and uniformity of the nanomaterials and reduces production costs.
Smart Images

Figure CN119118179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to a method for preparing nano materials based on active metal oxides and rare earth oxides. Background Art
[0002] Nanomaterials are ultrafine powders, generally referring to powders with a particle size of less than 100 nanometers. At present, nanomaterials are generally synthesized by solution method, gas phase method, electrochemical method, etc. Among them, the solution method is one of the most commonly used methods for synthesizing nanomaterials, which is divided into sol-gel method, precipitation method and liquid phase synthesis method. The advantages of the solution method are simple operation, conducive to large-scale synthesis, and the ability to obtain nanomaterials at a lower temperature. However, in order to obtain nanomaterials with smaller grain sizes, nanomaterials synthesized by the solution method usually need to be calcined at low temperatures, which will cause uneven particle size distribution and irregular morphology, as well as the problem that organic matter cannot be fully burned during the calcination process, which will lead to residual trace carbon elements in the nanomaterials. For some sensitive materials, the residual trace carbon elements will have an adverse effect on the electrical and optical properties of the material. The gas phase method is another commonly used synthesis method for nanomaterials, which includes thermal evaporation, physical vapor deposition and chemical vapor deposition. Compared with the solution method, the nanomaterials synthesized by this method have higher purity and better crystal structure. However, this method needs to be carried out under high vacuum and high temperature conditions, the synthesis process is relatively complicated, and the cost is high. The electrochemical method is a selective synthesis method that controls the size and morphology of particles by controlling voltage and current. This method is suitable for nanomaterials with complex crystal structures and special morphological requirements. Since this method takes a long time to synthesize nanomaterials and involves electrolytes, electrodes and other issues during the synthesis process, it is relatively complicated and not suitable for large-scale production.
[0003] As for the existing methods for synthesizing nanomaterials, the solution method is the most commonly used method. However, in the synthesis of nanomaterials, the sol-gel method is not easy to mass produce. Although the biggest advantage is the low calcination temperature, the crystal morphology of the nanomaterial is not very ideal. In addition, the carbon element in the material is not easy to be completely discharged. It is necessary to calcine and discharge carbon in an oxygen atmosphere, and there will be trace amounts of carbon elements remaining. Increasing the calcination temperature to discharge carbon is a feasible method, but it will also lead to abnormal growth of the grain size, and the ideal nanomaterial size cannot be obtained. The biggest advantage of the precipitation method is low cost and large-scale production, but since it is difficult to achieve precise control of the pH control, the obtained material still has problems in terms of uniformity. The advantages of the liquid phase synthesis method are easy operation, simple synthesis process, uniform particle size, controllable particle size, less pollution, and can avoid or reduce the hard agglomeration phenomenon that is easy to appear in the liquid phase, and low cost. However, the disadvantages are that the composition is not easy to be uniform, the particles are easy to agglomerate, and the powder particle size distribution is wide.
[0004] At present, how to solve the problems of carbon residue, easy agglomeration, uneven particle size distribution, calcination under atmosphere, and low material purity in the synthesis of nanomaterials is an urgent problem to be solved. The raising of this problem has put forward more urgent requirements for technicians in the field to develop nanomaterials with superior performance and low cost. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a nanomaterial with low calcination temperature, controllable grain morphology, no carbon residue and high powder purity, so as to improve the purity, uniformity and other properties of the nanomaterial and reduce the production cost of synthesizing the material.
[0006] To achieve the above object, the technical solution adopted in the present invention is as follows: The preparation method of the nano material based on active metal oxide and rare earth oxide comprises the following steps: Step 1, adding active metal oxide and rare earth oxide to nitric acid for initial hydrolysis to obtain a dissolved product, placing the dissolved product in a 90° C. water bath, heating and stirring until all dissolved to obtain a solution A, and adjusting the pH value of the solution A to 5-6.5; the molar ratio of nitric acid, active metal oxide and rare earth oxide is (10-16):2:(0.95-1.05); Step 2, filtering solution A, adding citric acid solution, the ratio of the amount of citric acid solution to the total amount of active metal ions in the active metal oxide and the rare earth metal ions in the rare earth oxide is 1-1.3:1; then adding ethylene glycol solution with a molar mass fraction of 0.5-5%, stirring until the mixture is uniformly mixed; then adding methanol solution with a molar mass fraction of 0.5-3%, stirring until the mixture is uniformly mixed, to obtain solution B; Step 3, evaporating solution B into a viscous colloid. Since the metal ions (active metal ions and rare earth metal ions) preferentially combine with the citric acid solution in step 2, the probability of the metal ions connecting with the carbon element in the colloid (organic matter) is reduced; Step 4, drying the colloid into foam, crushing and sieving the foam to obtain organic foam powder; Step 5: Place the organic foam powder in deionized water for secondary hydrolysis, then filter, wash and dry to obtain a white powder. The secondary hydrolysis can directly promote the breaking of the chemical bond between the metal ions and the organic matter in the metal salt organic matter, wherein the metal ions are converted into complexes or crystalline hydrates of the corresponding hydroxides (Mg(OH)2, Al(OH)3, Y(OH)3) to form precipitates, and then filter and wash to remove soluble impurities and organic matter (carbonaceous matter) dissolved in water; Step 6: calcine the white powder in air or oxygen to obtain a high-purity magnesium oxide yttrium oxide nanocomposite ceramic material.
[0007] Furthermore, in step 1, the active metal oxide is one or two of magnesium oxide (MgO) and aluminum oxide (Al2O3), the rare earth oxide is yttrium oxide (Y2O3) and other rare earth oxides, and the amount ratio of yttrium oxide and other rare earth oxides is (0.95-1):(0-0.05).
[0008] Furthermore, other rare earth oxides include any one or more of gadolinium oxide, cerium oxide, neodymium oxide, erbium oxide, lanthanum oxide, and lutetium oxide; yttrium oxide can be partially replaced by other rare earth oxides.
[0009] Further, in step 5, the hydrolysis reaction equation of the secondary hydrolysis is as follows: X n Y m (C6H5O7) X (NO3) 3m+2n-x +(3m+2n)H2O→nMg(OH)2+mY(OH)3+xC6H5O7 - +(3m+2n-x)NO3 - +(3m+2n) / 2H - ; X n Y m (C6H5O7) X (NO3) 3m+2n-x is the chemical formula of the polymer in the organic foam powder, and X is the metal ion in the active metal oxide.
[0010] Furthermore, in step 1, deionized water is used as a medium in the initial hydrolysis process to obtain a hydrolysis solution containing a dissolved substance, and the molar concentration of the hydrolysis solution is 0.5-1.5 mol / L.
[0011] Furthermore, in step 2, the molar concentration of the citric acid solution is 0.5-1.5 mol / L.
[0012] Furthermore, in step 4, the drying temperature is 110-180° C., the drying time is 5-8 hours, and the mesh size of the sieve used for sieving is 80-300.
[0013] Furthermore, in step 5, the volume of deionized water is 10-50 times the volume of the organic foam powder.
[0014] Furthermore, in step 5, the time of the secondary hydrolysis is 1-5h.
[0015] Furthermore, in step 6, the calcination temperature is 600° C. to 850° C. and the calcination time is 4 to 24 hours.
[0016] The problems of organic matter residue, carbon element residue, uneven distribution of components and uneven particle size in the large-scale production of nanomaterials, as well as the problem of calcining powder in the air, the key lies in how to remove organic matter, carbon element and other impurities before calcination, and how to avoid uneven components, and then realize calcination in an air environment and complete chemical reactions under low-temperature calcination. The present invention is different from the traditional liquid phase method, especially the sol-gel method. In the traditional liquid phase method, in each chemical reaction link during the synthesis process, the hydrolyzed active metal elements such as Mg 2+ 、Al 3+ , Y 3+ The carbon element is connected to the generated colloid (organic matter), that is, the molecular bond formed with the organic matter. The molecular bond belongs to ionic bond or covalent bond. In the subsequent process, the carbon element will always form a bond with the metal element. Whether it is in the process of forming sol-gel or in the process of polymerization reaction, the bond always exists. During the calcination process, especially when encountering insufficient oxygen, residual organic matter or residual carbon element may appear. In addition, calcination in air atmosphere may also result in insufficient reaction, and impurities and other carbon-containing substances cannot be eliminated.
[0017] The present invention hydrolyzes active metal oxides and rare earth oxides with nitric acid and then heats them to obtain a solution containing complexes and unreacted metal elements; then multiple solutions are added to achieve atomic-level uniformity on the one hand, ensuring that the electrical and mechanical properties of the synthesized nanomaterials will not be inconsistent in microscopic and macroscopic dimensions due to uneven mixing; on the other hand, a network of organic matter is formed, and citric acid is used to remove metal elements in the form of ions through bond valence; then the organic matter in solution B is evaporated into a colloid, further foamed to undergo a polymerization reaction to generate a polymer, the foamed substance is crushed into a tiny powder, and then the powder is subjected to secondary hydrolysis: when the active metal oxide is magnesium oxide (MgO), the hydrolysis reaction equation is: Mg n Y m (C6H5O7) X (NO3) 3m+2n-x +(3m+2n)H2O→nMg(OH)2+mY(OH)3+xC6H5O7 - +(3m+2n-x)NO3 - +(3m+2n) / 2H - ; When the active metal oxide is aluminum oxide (Al2O3), the hydrolysis reaction equation is: Al n Y m (C6H5O7) X (NO3) 3m+2n-x +(3m+2n)H2O→nAl(OH)2+mY(OH)3+xC6H5O7 -+(3m+2n-x)NO3 - +(3m+2n) / 2H - ; When the active metal oxides are magnesium oxide (MgO) and aluminum oxide (Al2O3), the hydrolysis reaction equation is: Mg n1 Al n2 Y m (C6H5O7) X (NO3) 3(n2+m)+2(n1)-x +3(n2+m)+2(n1)H2O→n2Al(OH)2+mY(OH)3+xC6H5O7 - +(3(n2+m)+2(n1)-x)NO3 - +(3(n2+m)+2(n1)) / 2H - . Since the hydrolysis conditions occur in an aqueous solution, there is no need to add acid or alkali to adjust the pH value in this process, and the metal elements (active metal ions and rare earth metal ions) are also uniformly mixed at the atomic level, so the obtained hydrolyzed material has atomic-level uniformity. After hydrolysis, a white powder containing Mg, Al, Y ions (Mg(OH)2, Al(OH)3, Y(OH)3, all of which are inorganic high-activity mixed materials) will be obtained, which is easy to remove. In the secondary hydrolysis process, water-soluble impurities (such as Na, K ions and their compounds) can be removed, and the organic matter and carbon-containing substances that are not completely foamed and remain are cleaned and removed to obtain high-purity inorganic powder, which is calcined to obtain a nanomaterial with uniform composition.
[0018] The removal of impurities, organic matter or carbon elements in the present invention is not removed by high-temperature calcination chemical reaction, but by secondary hydrolysis reaction, and then calcined at high temperature to break the OH bond in the corresponding complex or crystalline hydrate of the metal ion in the white powder, thereby obtaining a nanomaterial containing the corresponding metal oxide. The present invention removes the molecular bond between the metal element and the organic matter through secondary hydrolysis reaction, and based on the characteristics of Mg, Al, Y and other ions, a hydrolysis reaction can occur and a precipitate can be generated without adding acid or alkali to adjust the pH value (different from the traditional coprecipitation method), and then filtered and washed to remove soluble impurities, organic matter and carbon-containing substances (citric acid, ethylene glycol, methanol, etc.), etc., to obtain a carbon-free intermediate product (white powder). The intermediate product (white powder) obtained by secondary hydrolysis has the characteristics of higher purity and better uniformity, and it is precisely because it has the characteristics of high activity and no carbon element, so when calcined in air and at a lower temperature, a chemical reaction can quickly occur to synthesize a nanomaterial with high purity, high uniformity and low synthesis cost. In the present invention, the metals are uniformly mixed in the solution in the form of ions, so the obtained foam powder and the substance obtained by hydrolysis are also uniformly mixed at the ion level. The uniform mixing at the ion level can improve the uniformity of the nano material.
[0019] The present invention also adds ethylene glycol and methanol for two reasons. First, in the process of forming organic matter, there may be a situation where metal ions cannot combine with citric acid to form a bond, and ethylene glycol and methanol can assist the combination of the two. Second, the addition of ethylene glycol and methanol can promote the polymerization reaction of the colloid during the drying process, which can make the foamed foam have more and smaller pores and more uniform pores. In addition, it can reduce the covalent bond energy between polymer macromolecules in the colloid, so that the metal elements connected to the carbon bonds of the polymer can form small particles of inorganic matter during the hydrolysis reaction.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention removes soluble impurity ions and carbon-containing organic matter through a secondary hydrolysis reaction, thereby improving the purity of the nanomaterial, thereby improving the shortcomings of existing nanomaterials and improving the performance of the nanomaterials.
[0021] (2) Since the secondary hydrolysis reaction of the present invention does not require the adjustment of pH to be realized, the intermediate product obtained has better chemical activity and uniform composition than the material prepared by the traditional method, thereby making the calcined nanomaterial grain morphology more complete and the composition more uniform.
[0022] (3) The process of the present invention is simple to operate, low in cost and high in production efficiency. Different from the traditional process of calcination under oxygen atmosphere, nanopowder with higher purity can be obtained by calcination under air atmosphere and low temperature, which is conducive to improving the production efficiency of enterprises. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the XRD pattern of the white powder obtained in Example 1.
[0024] Figure 2 is the XRD pattern of the white powder obtained in Example 4. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In the embodiment of the present invention, the active metal oxide is magnesium oxide, the rare earth oxides are yttrium oxide and other rare earth oxides, and the amount ratio of yttrium oxide and other rare earth oxides is (0.95-1):(0-0.05).
[0027] In the embodiment of the present invention, other rare earth oxides include any one or more of gadolinium oxide, cerium oxide, neodymium oxide, erbium oxide, lanthanum oxide, and lutetium oxide; yttrium oxide can be partially replaced by other rare earth oxides.
[0028] As a preferred embodiment of the present invention, the method for preparing a nanomaterial based on active metal oxides and rare earth oxides provided in this embodiment comprises the following steps: Step 1, adding 1 mol of magnesium oxide and 0.5 mol of yttrium oxide to 5 mol of nitric acid and using deionized water as a medium for initial hydrolysis to obtain a dissolved product, placing the dissolved product in a 90° C. water bath, heating and stirring until all dissolved to obtain a solution A, and adjusting the pH value of the solution A to 5.5; Step 2, filter solution A, add 1.95 mol of 0.5 mol / L citric acid solution; then add 0.5% ethylene glycol solution, stir for 1 hour until mixed; then add 1% methanol solution, stir for 2 hours until mixed, to obtain solution B; Step 3, placing solution B in a water bath and evaporating for 36 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven at 110° C. and drying for 8 hours to obtain foam, and then crushing the foam and passing it through a 200-mesh sieve to obtain an organic foam powder; Step 5, placing the organic foam powder into deionized water with a volume 25 times that of the organic foam powder for secondary hydrolysis for 3 hours, and then filtering, washing, and drying to obtain a white powder; Step 6: The white powder is placed in air and calcined at 650° C. for 24 hours to obtain nanomaterial #1.
[0029] As a preferred embodiment of the present invention, the method for preparing a nanomaterial based on active metal oxides and rare earth oxides provided in this embodiment comprises the following steps: Step 1, add 5 mol nitric acid to 1 mol magnesium oxide, 0.475 mol yttrium oxide, and 0.025 mol lanthanum oxide and use deionized water as a medium for initial hydrolysis to obtain a dissolved product, place the dissolved product in a 90° C. water bath, heat and stir until all dissolved to obtain a solution A, and adjust the pH value of the hydrolyzate to 6; Step 2, filter solution A, add 1.5 mol of 0.5 mol / L citric acid solution; then add 5% ethylene glycol solution, stir for 1.5 hours until mixed; then add 3% methanol solution, stir for 1 hour until mixed, to obtain solution B; Step 3, placing solution B in a water bath and evaporating for 48 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven at 150° C. and drying for 6 hours to obtain foam, and then crushing the foam and passing it through a 300-mesh sieve to obtain an organic foam powder; Step 5, placing the organic foam powder into deionized water with a volume 32 times that of the organic foam powder for secondary hydrolysis for 4 hours, and then filtering, washing, and drying to obtain a white powder; Step 6: The white powder was calcined in air at 750° C. for 15 h to obtain nanomaterial #2.
[0030] As a preferred embodiment of the present invention, the method for preparing a nanomaterial based on active metal oxides and rare earth oxides provided in this embodiment comprises the following steps: Step 1, 2 mol of magnesium oxide, 0.97 mol of yttrium oxide, 0.02 mol of gadolinium oxide, and 0.01 mol of europium oxide are added to 10 mol of nitric acid and initially hydrolyzed using deionized water as a medium to obtain a dissolved product, the dissolved product is placed in a 90° C. water bath, heated and stirred until all dissolved to obtain a solution A, and the pH value of the hydrolyzate is adjusted to 5; Step 2, filter solution A, add 3 mol of 1 mol / L citric acid solution; then add 4% ethylene glycol solution, stir for 2 hours until mixed; then add 0.5% methanol solution, stir for 2 hours until mixed, to obtain solution B; Step 3, placing solution B in a water bath and evaporating for 72 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven at 120° C. and drying for 7 hours to obtain foam, and then crushing the foam and passing it through a 200-mesh sieve to obtain an organic foam powder; Step 5, placing the organic foam powder into deionized water with a volume 15 times that of the organic foam powder for secondary hydrolysis for 1.5 hours, then filtering, washing, and drying to obtain a white powder; Step 6: calcine the white powder in air at 800° C. for 12 h to obtain nanomaterial #3.
[0031] As a preferred embodiment of the present invention, the method for preparing a nanomaterial based on active metal oxides and rare earth oxides provided in this embodiment comprises the following steps: Step 1, 1 mol of magnesium oxide, 0.49 mol of yttrium oxide, and 0.01 mol of cerium oxide are added to 5 mol of nitric acid and initially hydrolyzed using deionized water as a medium to obtain a dissolved product, the dissolved product is placed in a 90° C. water bath, heated and stirred until completely dissolved to obtain a solution A, and the pH value of the hydrolyzate is adjusted to 5.5; Step 2, filter solution A, add 1.5 mol of 1 mol / L citric acid solution; then add 3.5% ethylene glycol solution, stir for 1 hour until mixed; then add 1.5% methanol solution, stir for 1.5 hours until mixed, to obtain solution B; Step 3, placing solution B in a water bath and evaporating for 72 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven at 180°C and drying for 5 hours to obtain foam, and then crushing the foam and passing it through a 300-mesh sieve to obtain an organic foam powder; Step 5, placing the organic foam powder into deionized water with a volume 10 times that of the organic foam powder for secondary hydrolysis for 1 hour, and then filtering, washing, and drying to obtain a white powder; Step 6: calcine the white powder in air at 850° C. for 24 h to obtain nanomaterial #4.
[0032] As a preferred embodiment of the present invention, the method for preparing a nanomaterial based on active metal oxides and rare earth oxides provided in this embodiment comprises the following steps: Step 1, 3 mol of magnesium oxide, 1.47 mol of yttrium oxide, 0.015 mol of lutetium oxide, and 0.015 mol of gadolinium oxide are added to 15 mol of nitric acid and initially hydrolyzed using deionized water as a medium to obtain a dissolved product, the dissolved product is placed in a 90° C. water bath, heated and stirred until all dissolved to obtain a solution A, and the pH value of the hydrolyzate is adjusted to 5.5; Step 2, filter solution A, add 4.5 mol of 1 mol / L citric acid solution; then add ethylene glycol solution with a molar mass fraction of 2.5%, stir for 2 hours until mixed evenly; then add methanol solution with a molar mass fraction of 1%, stir for 1.5 hours until mixed evenly, to obtain solution B; Step 3, placing solution B in a water bath and evaporating for 30 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven at 130° C. and drying for 7 hours to obtain foam, and then crushing the foam and passing it through a 200-mesh sieve to obtain an organic foam powder; Step 5, placing the organic foam powder into deionized water with a volume 50 times that of the organic foam powder for secondary hydrolysis for 5 hours, and then filtering, washing, and drying to obtain a white powder; Step 6: calcine the white powder in air at 800° C. for 18 h to obtain nanomaterial #5.
[0033] As a preferred embodiment of the present invention, the method for preparing a nanomaterial based on active metal oxides and rare earth oxides provided in this embodiment comprises the following steps: Step 1, add 1 mol of aluminum oxide and 0.5 mol of yttrium oxide to 6 mol of nitric acid and use deionized water as a medium for initial hydrolysis to obtain a dissolved product, place the dissolved product in a 90° C. water bath, heat and stir until all dissolved to obtain a solution A, and adjust the pH value of the solution A to 5.5; Step 2, filter solution A, add 3.5 mol of 0.5 mol / L citric acid solution; then add 0.5% ethylene glycol solution, stir for 1 hour until mixed; then add 1% methanol solution, stir for 2 hours until mixed, to obtain solution B; Step 3, placing solution B in a water bath and evaporating for 36 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven at 110° C. and drying for 8 hours to obtain foam, and then crushing the foam and passing it through a 200-mesh sieve to obtain an organic foam powder; Step 5, placing the organic foam powder into deionized water with a volume 25 times that of the organic foam powder for secondary hydrolysis for 3 hours, and then filtering, washing, and drying to obtain a white powder; Step 6: calcine the white powder in air at 650° C. for 24 h to obtain nanomaterial #1.
[0034] As a preferred embodiment of the present invention, the method for preparing a nanomaterial based on active metal oxides and rare earth oxides provided in this embodiment comprises the following steps: Step 1, 1 mol of magnesium oxide, 1 mol of aluminum oxide, 1.47 mol of yttrium oxide, 0.015 mol of lutetium oxide, and 0.015 mol of gadolinium oxide are added to 8 mol of nitric acid and initially hydrolyzed using deionized water as a medium to obtain a dissolved product, the dissolved product is placed in a 90° C. water bath, heated and stirred until all dissolved to obtain a solution A, and the pH value of the hydrolyzate is adjusted to 5.5; Step 2, filter solution A, add 5.53 mol of 1 mol / L citric acid solution; then add 2.5% ethylene glycol solution, stir for 2 hours until mixed; then add 1% methanol solution, stir for 1.5 hours until mixed, to obtain solution B; Step 3, placing solution B in a water bath and evaporating for 30 hours to obtain a viscous colloid; Step 4, placing the colloid in an oven at 130° C. and drying for 7 hours to obtain foam, and then crushing the foam and passing it through a 200-mesh sieve to obtain an organic foam powder; Step 5, placing the organic foam powder into deionized water with a volume 50 times that of the organic foam powder for secondary hydrolysis for 5 hours, and then filtering, washing, and drying to obtain a white powder; Step 6: calcine the white powder in air at 800° C. for 18 h to obtain nanomaterial #5.
[0035] The particle size and impurity content of the nanomaterials prepared in Examples 1 to 5 were tested by X-ray diffraction. The test results are shown in Table 1 below.
[0036] Table 1
[0037] According to the data in Table 1, the nanomaterial prepared by the present invention has a good particle size distribution, is characterized by high purity, has little residual impurities such as carbon elements, and can be calcined in an air environment, which significantly improves the quality and stability of the product. In addition, the production raw materials are cheap, and the preparation process is compatible with traditional processes, which is conducive to improving the production efficiency of the enterprise.
[0038] like Figure 1 and Figure 2 As shown, the white powders obtained in Example 1 and Example 4 contain complexes of metal hydroxides or complex substances containing crystal water, and do not contain carbon-containing substances.
[0039] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A method for preparing nanomaterials based on active metal oxides and rare earth oxides, characterized in that: The following steps are involved: Step 1, adding active metal oxide and rare earth oxide to nitric acid for initial hydrolysis to obtain a dissolved product, placing the dissolved product in a 90° C. water bath, heating and stirring until all dissolved to obtain a solution A, and adjusting the pH value of the solution A to 5-6.5; the molar ratio of nitric acid, active metal oxide and rare earth oxide is (10-16):2:(0.95-1.05); Step 2: Filter solution A and add citric acid solution. The amount of citric acid solution is The total amount ratio of active metal ions in active metal oxides to rare earth metal ions in rare earth oxides is 1-1.3:1; then, 0.5-5% ethylene glycol solution is added, and stirred until the mixture is uniformly mixed; then, 0.5-3% methanol solution is added, and stirred until the mixture is uniformly mixed to obtain solution B; Step 3, evaporating solution B into a viscous colloid; Step 4, drying the colloid into foam, crushing and sieving the foam to obtain organic foam powder; Step 5, placing the organic foam powder in deionized water for secondary hydrolysis, and then filtering, washing, and drying to obtain a white powder; Step 6: calcine the white powder in air or oxygen to obtain nanomaterials.
2. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 1, characterized in that: In step 1, the active metal oxide is one or both of magnesium oxide and aluminum oxide, the rare earth oxide is yttrium oxide and other rare earth oxides, and the amount ratio of yttrium oxide and other rare earth oxides is (0.95-1):(0-0.05).
3. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 2, characterized in that: Other rare earth oxides include any one or more of gadolinium oxide, cerium oxide, neodymium oxide, erbium oxide, lanthanum oxide, and lutetium oxide; yttrium oxide can be partially replaced by other rare earth oxides.
4. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 2, characterized in that: In step 5, the hydrolysis reaction equation of the secondary hydrolysis is as follows: <h2 style=";text-align:left;direction:ltr">X<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> (C6H5O7)<h2 style=";text-align:left;direction:ltr"> X <h2 style=";text-align:left;direction:ltr"> (NO3)<h2 style=";text-align:left;direction:ltr"> 3m+2n-x <h2 style=";text-align:left;direction:ltr"> +(3m+2n)H2O→nMg(OH)2+mY(OH)3+xC6H5O7<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> +(3m+2n-x)NO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> +(3m+2n) / 2H<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> ; X n Y m (C6H5O7) X (NO3) 3m+2n-x is the chemical formula of the polymer in the organic foam powder, and X is the metal ion in the active metal oxide.
5. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 1, characterized in that: In step 1, deionized water is used as a medium in the initial hydrolysis process to obtain a hydrolysis solution containing a dissolved substance, and the molar concentration of the hydrolysis solution is 0.5-1.5 mol / L.
6. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 1, characterized in that: In step 2, the molar concentration of the citric acid solution is 0.5-1.5 mol / L.
7. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 1, characterized in that: In step 4, the drying temperature is 110-180° C., the drying time is 5-8 hours, and the mesh number of the sieve used for sieving is 80-300.
8. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 1, characterized in that: In step 5, the volume of deionized water is 10-50 times the volume of the organic foam powder.
9. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 1, characterized in that: In step 5, the time of secondary hydrolysis is 1-5h.
10. The method for preparing nanomaterials based on active metal oxides and rare earth oxides according to claim 1, characterized in that: In step 6, the calcination temperature is 600° C. to 850° C. and the calcination time is 4 to 24 hours.
